The dual-serving problem: What is the right choice of inventory strategy?. (September 2021) - Mahdavi, Mojtaba; Olsen, Tava Lennon
Highlights: Aggregating all classes of demand is not always an optimal inventory strategy. Inventory rationing can outperform a first-come-first-served approach. Design and optimality of an inventory strategy depend of demand characteristics. Demand aggregation works better when demand variability is high. Protection strategy works better when procurement cost is high. Abstract: This paper defines and explores a dual-serving problem from the lens of inventory management. The problem arises when a supplier faces two different types of demand, i.e., one that is very frequent and regular, but in small quantities, while the other is sporadic and irregular, but in very large quantities. The former is easier to manage because of its greater predictability, while the latter can be of higher importance as it constitutes the majority of the annual sales. Such dual serving is becoming a significant problem in the online retail sector due to the increasing prevalence of daily deals platforms. We first investigate whether and in what circumstances the supplier is better off serving both types of demand. Then, we compare the performance of a conventional demand aggregation approach in the continuous review model with a particular inventory rationing strategy called protection, both at their optimal settings.